2012
DOI: 10.1210/jc.2012-1123
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Surveillance of Papillary Thyroid Cancer Patients Who Do Not Undergo Postoperative Radioiodine Remnant Ablation: Is There a Role for Serum Thyroglobulin Measurement?

Abstract: In most RRA-negative patients, postoperative serum Tg values spontaneously drop to undetectable levels within 5-7 yr after thyroidectomy. Thus, in later phases, Tg assays may be a valuable tool for follow-up even in patients who do not undergo RRA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
69
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(77 citation statements)
references
References 20 publications
5
69
0
3
Order By: Relevance
“…First, we could not validate the dynamic risk stratification system for patients who did not receive RAI ablation therapy or for those who did lobectomy because we only included patients who underwent total or near total thyroidectomy followed by RAI ablation, which made relatively homogenous characteristics and less confounding factors for analysis. A recent study suggested that the serum Tg level may also be useful during the follow-up period and it can predict outcomes for patients who did not receive RAI ablation therapy (27). In this regard, further studies are required to validate whether the dynamic risk stratification system could be useful for patients who did not receive RAI ablation therapy.…”
Section: Discussionmentioning
confidence: 99%
“…First, we could not validate the dynamic risk stratification system for patients who did not receive RAI ablation therapy or for those who did lobectomy because we only included patients who underwent total or near total thyroidectomy followed by RAI ablation, which made relatively homogenous characteristics and less confounding factors for analysis. A recent study suggested that the serum Tg level may also be useful during the follow-up period and it can predict outcomes for patients who did not receive RAI ablation therapy (27). In this regard, further studies are required to validate whether the dynamic risk stratification system could be useful for patients who did not receive RAI ablation therapy.…”
Section: Discussionmentioning
confidence: 99%
“…This assessment is based on well-known TNM staging which determines mortality but not the risk of recurrence. Recurrence assessment system proposed by 2015 ATA guideline (Tables 2 and 3) is a reliable predictor for the course of diferentiated thyroid carcinoma treated with thyroidectomy alone or radioiodine remnant ablation [57][58][59][60].…”
Section: Managementmentioning
confidence: 99%
“…To our knowledge, this is so far the first prospective study that evaluated tumor recurrence in patients with low postoperative nonstimulated Tg, who were not treated with 131 I because of this result. In contrast to previous studies in which most of the patients had microcarcinoma restricted to the thyroid (Durante et al 2012, Ibrahimpasic et al 2012, Nascimento et al 2013, Angell et al 2014, these patients and those with noninvasive E-FVPTC (Rosario et al 2014a) were excluded from the present study because there is consensus that ablation of thyroid remnant is not necessary in these cases. More than half the patients were older than 45 years and 2 of 3 had a multicentric tumor O1 and %4 cm (T1b-2Nx), tumor O4 cm or with extrathyroid invasion (T3Nx), or clinically apparent LN metastases (T1-2cN1).…”
Section: Discussionmentioning
confidence: 99%
“…The rate of recurrence was the same (3 of 112 (2.6%)) when only patients with a follow-up time O5 years were analyzed. Even when measured with a second-generation assay, undetectable or low nonstimulated Tg can be achieved in many patients submitted to total thyroidectomy (Giovanella et al 2008, Durante et al 2012, Nascimento et al 2013, Angell et al 2014, Rosario et al 2015a, 2015b. In these patients, two studies have shown that RxWBS did not reveal persistent disease in any case after the administration of 131 I (1.1-3.7 GBq; Giovanella et al 2008, Rosario et al 2015a.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation